Aboveground biomass of marshes in Northeast China: Spatial pattern and annual changes responding to climate change - Ren, Yongxing; Mao, Dehua; Li, Xiaoyan; Wang, Zongming; Xi, Yanbiao; Feng, Kaidong (Frontiers in Ecology and Evolution, 2022)
Examining vegetation aboveground biomass (AGB) changes is important to understanding wetland carbon sequestration. Here we combined the field measured AGB data (458 samples) from 2009 to 2021, moderate resolution imaging spectroradiometer (MODIS) reflectance products, and climatic data to reveal the AGB variations of marshes in Northeast China by comparing various models driven by different indicators. The results indicated that random forest model driven by six vegetation indices, land surface temperature, and land surface water index achieved accurate marsh AGB estimation with R2 being 0.78 and relative error being 16.71%. The mean marsh AGB in Northeast China from 2000 to 2021 was 682.89±31.69 g⋅m-2, which generally increased from north to south in space. Temporally, annual marsh AGB declined slowly at a rate of 3.45 g⋅m-2⋅year-1 during the past 21 years driven mainly by the decrease in summer mean temperature that was characterized by a significantly positive correlation between them. Nevertheless, we highlighted that the temporal changes of marsh AGB spatially varied in response to inconsistent climate change, thus place-based measures are required for sustainable management of marshes.